EVALUASI PENYIMPANAN DAN PENDISTRIBUSIAN VAKSIN COVID-19 DI DINAS KESEHATAN PROVINSI SULAWESI TENGAH - Diana, Khusnul; Ekasandra, Nur; Tandah, Muhamad Rinaldhi (Jurnal Insan Farmasi Indonesia, 2023)
The Health Department is responsible for distributing COVID-19 vaccines in the region. This research was conducted to evaluate the suitability of storage and distribution  in the warehouse of the Pharmaceutical Installation of the Central Sulawesi Health Department, following the guidelines set in the Director General of Disease Prevention and Control Decision Number Hk.02.02/4/1/2021. The research used observational and qualitative descriptive methods, collecting data within a specific period, using all COVID-19 vaccines stored in the Pharmaceutical Installation of the Central Sulawesi Health Department as the sample. The research results show  8 types of COVID-19 vaccines managed by the Central Sulawesi Health Department, divided into 3 groups: vaccines that must be stored at 2-8 ºC, vaccines that must be stored at -20 ºC, and vaccines that must be stored at -70ºC. All groups of vaccines comply with the guidelines at 100%. However, concerning distribution, the level of compliance hasn't reached 100%. The group of vaccines that must be stored at 2-8 ºC, the compliance percentage is 63.64%. Similarly, the group of vaccines that must be stored at -20 ºC, the compliance percentage is also 63.64%, and the group of vaccines that must be stored at -70 ºC, the compliance percentage reaches 69.23%.